ASSOCIATION OF PROLACTIN GENE POLYMORPHISM WITH EGG PRODUCTION TRAIT IN LIEN MINH CHICKEN - Binh Nguyen, Tran Thi; Duc, Nguyen Huu; Dieu Thuy, Nguyen Thi (Vietnam Journal of Biotechnology, 2018)
Lien Minh chicken is an indigenous breed with several favorable properties, such as good meat quality and associated with the economic development of the people in the Lien Minh village, Cat Hai, Hai Phong. Chicken prolactin is a candidate gene involved in egg production trait. The aim of this study was to investigate the association of single nucleotide polymorphism (SNP) of Prolactin gene (PRL) concerning with reproductive trait in Lien Minh chicken. All hens were kept in individual laying cage and phenotypic data for total 90 hens were recorded as following: age at first egg, first egg’s weight, number of eggs, eggs’ weight, and eggs’ shape index. Blood samples were used for DNA extraction and then genotyping by PCR-RFLP method. Two SNPs of PRL gene were analyzed including: 24 bp indel in promoter (PRL24) and C2402T in 5' flanking region (PRL5). The polymorphic sites at PRL24 and PRL5 showed two genotypes with the frequency of ID (0.27), DD (0.73) and CT (0.41), TT (0.59), respectively. Allele frequencies of PRL24 and PRL5 were: I (0.13), D (0.87) and C (0.21), T (0.79), respectively. Genotypes ID PRL24 and CT at PRL5 showed the highest values of mean weight of eggs 47.57 ± 3,11 g and 46.91 ± 4.29 g, respectively (P < 0.05). In addition, the individual with genotype ID, CT also gave better reproductive characteristics such as number of eggs, first egg’s weight. These results suggested that the beneficial alleles/genotypes could be used to support the improvement of the egg production capacity in the breeding of Lien Minh chicken.